Electroweak processes in external active media - Kuznetsov, Alexander (Springer Tracts in Modern Physics, 2013)
Expanding on the concept of the authors' previous book "Electroweak Processes in External Electromagnetic Fields," this new book systematically describes the investigation methods for the effects of external active media, both strong electromagnetic fields and hot dense plasma, in quantum processes. Solving the solar neutrino puzzle in a unique experiment conducted with the help of the heavy-water detector at the Sudbery Neutrino Observatory, along with another neutrino experiments, brings to the fore electroweak physics in an active external medium. It is effectively demonstrated that processes of neutrino interactions with active media of astrophysical objects may lead, under some physical conditions, to such interesting effects as neutrino-driven shockwave revival in a supernova explosion, a "cherry stone shooting" mechanism for pulsar natal kick, and a neutrino pulsar. It is also shown how poor estimates of particle dispersion in external active media sometimes lead to confusion. The book will appeal to graduate and post-graduate students of theoretical physics with a prior understanding of Quantum Field Theory (QFT) and the Standard Model of Electroweak Interactions, as well as to specialists in QFT who want to know more about the problems of quantum phenomena in hot dense plasma and external electromagnetic fields.